Perceived Effects of Elephants (Loxodonta africana Cuvier) Presence and Impacts on Ecosystem Services Supply in the Pendjari Biosphere Reserve, West Africa - Gnonlonfoun, Isidore; KASSA, DAHOGA BARTHÉLÉMY; AZIHOU, AKOMIAN FORTUNÉ; Mensah, Sylvanus; GLELE KAKAÏ, A. ROMAIN LUCAS; ASSOGBADJO, ACHILLE EPHREM (My University, 2019)
Information on how biotic factors influence delivery of ecosystem services (ES) in natural systems is important for holistic landscape management. In this study, we assessed the perceived effects of elephants’ presence on ES supply in the Pendjari Biosphere Reserve in West Africa. A total of 112 respondents, including riparian communities and reserve officials, were interviewed. First, we used ranking techniques based on stakeholders’ perceptions to evaluate differences in perceived importance of ES. Second, we assessed the perceived impact of elephants on ES supply from both direction and intensity perspective. Third, we assessed the economic importance of threatened ESs and elephants’ damages related economic losses incurred by households. Twenty-seven ES were enumerated, 13 provisioning ES, 12 cultural ES, and two from the regulating and maintenance ES category. Provisioning ES were perceived as the most important although not significantly different from other categories. PES were also found to be most affected negatively by elephants’ impacts. However, elephants’ presence increased supply of cultural ES. The average cost of the losses due to elephants’ negative impacts ranged from $174.80 to $586.05 per year and per victim household. These results were discussed in relation to management actions necessary to facilitate coexistence between elephant and local populations.
Keywords: biotic disturbances; ecosystem services; perceptions; economic valuation; protected areas